Formulasi Whey Fermentasi dengan Penambahan Buah Merah (Pandanus conoideus Lam) sebagai Tabir Surya - M. Ranggawati; I. I. Arief; Z. Wulandari (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2022)
Whey produced from cheese processing can be used as non-food products such as sunscreen by fermenting using Streptococcus thermophilus and Lactobacillus bulgaricus. Adding active ingredients such as red fruit oil which contains carotenoids can increase the effectiveness of sunscreen. This study aims to determine the formulation of fermented whey and red fruit oil usage in sunscreen. The study began with the production of fermented whey and sunscreen formulations with ratios of 0, 1:1, 1:2, and 2:1 (fermented whey: red fruit oil). Furthermore, observe the organoleptic, antioxidant, SPF, pH, and homogeneity value. Adding fermented whey and red fruit oil showed no significant effect (P>0.05) onthe organoleptic test of aroma, but significantly (P<0.05) on color and texture. The antioxidant activity value test showed significantly different results (P<0.05) with IC50 values classified as moderate to high.Determination of the SPF value of sunscreen showed significantly different results (P<0.05), but this value was classified as low protection. Although there was no significant effect on pH testing (P>0.05), the pH of sunscreen cream indicated that it was suitable for topical application. All samples showed homogeneous results and there were no coarse particles or separation between the oil and water phases. The best sunscreen formulation is 1:1 cream with the highest SPF value of 6.86 and strong antioxidant activity with an IC50 value of 56.15 g/mL. Fermented whey and red fruit oil usage as active ingredients are more effective in increasing the protection of the cream against UV rays and free radicals.